Synthesis and Applications of ZnO/Polymer Nanohybrids - Wang, Zongyu; Bockstaller, Michael R; Matyjaszewski, Krzysztof (ACS materials letters, 2021)
Because of its distinctive combination of physical properties such as high thermal conductivity, ultraviolet (UV) absorbance, or catalytic behavior, zinc oxide-based nanoparticles have attracted interest for the use as fillers to augment a wide range of physicochemical properties of polymer materials, including their optical, dielectric, thermal, and catalytic characteristics. To accomplish the desired property enhancements, precise control of the microstructure of polymer/zinc nanoparticle blends is a prerequisite. This requires the ability to tailor and control the interactions between particle fillers and the polymer matrix. Much progress in the field of polymer/ZnO hybrids has been achieved through the development of surface-initiated controlled radical polymerization (CRP) methods that allow for the deliberate modification of zinc oxide surfaces with polymer chains. The ensuing enhancement in particle compatibility has enabled the design of novel multifunctional polymer/ZnO nanocomposite materials. This article surveys recent advances in the application of surface polymerization techniques to enable novel zinc oxide (ZnO)/polymer hybrids. The evolution of synthetic strategies from the pioneering work using “grafting-from” to recently developed “grafting-onto” and “templated synthesis” methods is presented. Subsequently, the opportunities for the design of functional nanocomposite materials based on ZnO hybrids with applications in optics, catalysis, energy, and biomedical areas are being presented. We conclude by highlighting current challenges and opportunities for research in this exciting area of polymer materials research.